VEEP. [videorecording (DVD)] The complete fourth season. - Louis-Dreyfus, Julia; Chlumsky, Anna; Walsh, Matt, 1964- (HBO Home Box Office, 2016)
Former Senator Selina Meyer has accepted the call to serve as Vice President of the United States. The job is nothing like she imagined and everything she was warned about. 'Veep' follows Meyer and her staff as they attempt to make their mark and leave a lasting legacy, without getting tripped up in the day-to-day political games that define Washington.